Mode-locked near-infrared thulium doped fibre laser using evanescent field effect with Bi2O3 saturable absorber. (26th March 2019) - Ahmad, H; Monajemi, H; Thambiratnam, K; Ismail, M F
Abstract: Using the evanescent field effect, a high power passively mode-locked laser with a pulse duration of 1.85 ps and the pulse energy of 13.15 pJ is demonstrated. A Bi2 O3 solution is used as a saturable absorber (SA) on a side polished fibre incorporated into a thulium doped fibre laser cavity for operation in the mid-infrared range. The 37.61% SA has a modulation depth and creates a highly stable mode-locked pulse output with a short pulse duration. The calculated net cavity dispersion at central wavelength is −1.4 ps 2, indicating operation is in the anomalous dispersion regime and confirmed by the presence of Kelly's side-bands observed in the generated optical spectrum. Radio frequency analysis reveals a high signal to noise ratio, making this laser stable for use in telecommunication systems.